Effectiveness Test of Green Betel Leaf Extract (Piper betle L.) on the Growth of Candida albicans - Yohania Premita; Riris Grace Aprilia; Boyke Marthin Simbolon; Riyani Susan Bt. Hasan (HM Publisher, 2022)
Background: Candida albicans is a fungus that often results in opportunistic infections in humans, called candidiasis. People generally practice self-medication to treat candidiasis with azole antifungals. However, this causes resistance due to inappropriate drug or dose selection. Betel leaf extract, which contains active compounds with antifungal properties such as phenols, tannins, and flavonoids, can be used as alternative medicine. The purpose of this study was to determine whether there was an effect of green betel leaf extract (Piper betle L.) on the growth of Candida albicans. Methods: This study is an experimental study and uses the disc diffusion method. The betel leaf was extracted using the maceration method and made into concentrations of 40%, 60%, 80%, and 100%. Results: The mean inhibition zone diameters were 9.12 mm, 8.79 mm, 8.18 mm, and 8.55 mm at concentrations of 40%, 60%, 80%, and 100%, sequentially. Conclusion: Betel leaf extract has an antifungal effect, with the most effective concentration being 40%.